Reduced Efficacy of d-Amphetamine and 3,4-Methylenedioxymethamphetamine in Inducing Hyperactivity in Mice Lacking the Postsynaptic Scaffolding Protein SHANK1 - Sungur, A. Özge; Redecker, Tobias M.; Andres, Elena; Dürichen, Wiebke; Schwarting, Rainer K. W.; del Rey, Adriana; Wöhr, Markus (Frontiers in Molecular Neuroscience, 2018)
Genetic defects in the three SH3 and multiple ankyrin repeat domains (SHANK) genes (SHANK1, SHANK2, and SHANK3) are associated with multiple major neuropsychiatric disorders, including autism spectrum disorder (ASD), schizophrenia (SCZ), and bipolar disorder (BPD). Psychostimulant-induced hyperactivity is a commonly applied paradigm to assess behavioral phenotypes related to BPD and considered to be the gold standard for modeling mania-like elevated drive in mouse models. Therefore, the goal of our present study was to test whether Shank1 plays a role in the behavioral effects of psychostimulants and whether this is associated with genotype-dependent neurochemical alterations. To this aim, male and female null mutant Shank1-/- mice were treated with d-amphetamine (AMPH; 2.5 mg/kg) and 3,4-methylenedioxymethamphetamine (MDMA, commonly known as ecstasy; 20 mg/kg), and psychostimulant-induced hyperactivity was compared to heterozygous Shank1+/- and wildtype Shank1+/+ littermate controls. Results show that Shank1-/- mice display reduced psychostimulant-induced hyperactivity, although psychostimulants robustly stimulated locomotor activity in littermate controls. Shank1 deletion effects emerged throughout development, were particularly prominent in adulthood, and seen in response to both psychostimulants, i.e. AMPH and MDMA. Specifically, while AMPH-induced hyperactivity was reduced but still detectable in Shank1-/- mice, MDMA-induced hyperactivity was robustly blocked and completely absent in Shank1-/- mice. Reduced efficacy of psychostimulants to stimulate hyperactivity in Shank1-/- mice might be associated with alterations in the neurochemical architecture in prefrontal cortex, nucleus accumbens, and hypothalamus. Our observation that psychostimulant-induced hyperactivity is reduced rather than enhanced in Shank1-/- mice clearly speaks against a behavioral phenotype with relevance for BPD. Lack of BPD-like phenotype is consistent with currently available human data linking mutations in SHANK2 and SHANK3 to BPD but not SHANK1.